Retrospective analysis of urban malaria cases due to Plasmodium falciparum and Plasmodium vivax: the case of Batu town, Oromia, Ethiopia - Jifar Hassen; Hunduma Dinka (Heliyon, 2020)
Malaria is a major health problem in the world particularly in sub-Saharan Africa where 90% of malaria deaths occur. Likewise malaria is one of the leading causes of morbidity and mortality in Ethiopia. It has been reported that about 75% of the country is malarious where 60% of its population is at risk of this infection. Like many African countries, Ethiopian urban settings are characterized by poor housing, lack of sanitation and drainage of surface water which provide conducive environment for the breeding of vector mosquitoes for the transmission of malaria. There are few researches on urban malaria under the urban settings of Ethiopia. The purpose of this study was to assess the magnitude of malaria cases due to Plasmodium falciparum and Plasmodium vivax in Batu town, Oromia, Ethiopia. Retrospective laboratory confirmed malaria case record data of six years (2012–2017) were used to analyze the magnitude of malaria cases due to P. falciparum and P. vivax, in Batu town, Oromia, Ethiopia. The retrospective data analysis revealed an overall 21,797 malaria confirmed cases; of which 49.5% were due to P. falciparum and 50.5% were due to P. vivax, with a slight decline in malaria between 2012 and 2017. Malaria cases were recorded in both sexes and all age groups in the study area. From the result of the present analysis it can be concluded that both P. falciparum and P. vivax were the cause for malaria cases indicating malaria is still public health problem in Batu town. Therefore, appropriate strategic control measures must be designed to protect the public and eventually eliminate malaria from the area and the country as a whole.